2009
DOI: 10.1097/aln.0b013e3181ae63d1
|View full text |Cite
|
Sign up to set email alerts
|

Methoxycarbonyl-etomidate

Abstract: Background Etomidate is a rapidly-acting sedative-hypnotic that provides hemodynamic stability. However because it causes prolonged suppression of adrenocortical steroid synthesis, its clinical utility and safety are limited. We describe the results of studies to define the pharmacology of (R)-3-methoxy-3-oxopropyl1-(1-phenylethyl)-1H-imidazole-5-carboxylate (MOC-etomidate), the first etomidate analogue designed to be susceptible to ultra-rapid metabolism. Methods The γ-aminobutyric acid type A receptor acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
78
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 47 publications
5
78
1
Order By: Relevance
“…512 Our primarily goal was to create a drug that would retain etomidate’s highly desirable properties, but whose effects on adrenocortical function would lift quickly after drug administration because the drug was rapidly eliminated. At the same time, it was hoped that recovery from the drug’s hypnotic action would similarly be very rapid even after prolonged infusion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…512 Our primarily goal was to create a drug that would retain etomidate’s highly desirable properties, but whose effects on adrenocortical function would lift quickly after drug administration because the drug was rapidly eliminated. At the same time, it was hoped that recovery from the drug’s hypnotic action would similarly be very rapid even after prolonged infusion.…”
Section: Introductionmentioning
confidence: 99%
“…5 Similar to remifentanil and esmolol, it contains a metabolically labile ester moiety that is linked to the pharmacophore via a 2-carbon spacer. This spacer facilitates hydrolysis by esterases by reducing steric hindrance around the ester.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 We established proof-of-principle by synthesizing the prototypical “soft” ( i.e. , metabolically-labile) etomidate analogue methoxycarbonyl etomidate, but found that its pharmacological properties were not suitable for clinical development.…”
Section: Introductionmentioning
confidence: 99%
“…, metabolically-labile) etomidate analogue methoxycarbonyl etomidate, but found that its pharmacological properties were not suitable for clinical development. 19-22 Subsequent efforts at rational optimization of methoxycarbonyl etomidate's pharmacology led to the synthesis and study of more than a dozen new analogues, of which cyclopropylmethoxycarbonyl metomidate (CPMM, also known as ABP-700) exhibited the most promising pharmacology in rats (fig. 1) and became the lead candidate for advancement to human trials.…”
Section: Introductionmentioning
confidence: 99%